ELECTRON MICROSCOPIC AND SPERM FUNCTION STUDY OF SPERMATOZOA OF HOLSTEIN FRIESIAN BULL - SAINI, J; DHANDE, PL; GAIKWAD, SA; SHANKHAPAL, VD; DAGLI, NR (The Indian Journal of Animal Reproduction, 2017)
Semen samples were artificially collected from apparently healthy and sexually mature Holstein Friesian bulls (n=6; age, 4-6 yr). Transmission electron microscope revealed mature spermatozoon consisting of head covered by acrosome, neck had a depression continuous to middle piece which consisted of a flagellar core and fibers. The middle piece was followed by principal or main piece and terminated in an end piece. In sperm function test, 90.33±1.20% acrosome were intact and 87.67±2.08% sperms were hypo-osmotic swelling test reactive, thus indicating good quality of semen.
Keywords: Electron Microscope; Holstein Friesian; Micrometry; Spermatozoa; Sperm function